Weber's Social Action Analysis on the Phenomenon of Millennial Generation Marriage Postpone in Al-Quran Perspective - Yuniarsih, Krisma; Sumedi, Sumedi (Universitas Islam Negeri (UIN) Salatiga, 2024)
The phenomenon of postponing marriage among millennials indicates a change in mindset and life priorities due to the influence of modernity. This study aims to investigate the views and definition of marriage according to the millennial generation, the social factors that influence the millennial generation's decision to postpone marriage according to Weber's social action theory, and the Quranic (Islamic) perspective on this phenomenon. This research uses a qualitative approach with a library research method. Data were collected from previous research results, scientific journal articles, survey reports, and official statistical documents that discuss the marriage patterns of the millennial generation in the 2018-2025 timeframe, the Quran, hadith, and tafsir relevant to the theme of marriage and family formation. Data analysis was conducted through data categorization based on Weber's four types of social action, data interpretation, comparative analysis between empirical findings and Quranic perspectives, and conclusion drawing that integrates the two perspectives. The results of the analysis show that millennials postpone marriage to achieve financial stability, self-development, and emotional compatibility with partners. Emotional factors such as relationship trauma and expectations of an ideal marriage also influence this decision. Meanwhile, religious values emphasize the importance of balancing worldly and spiritual demands, providing guidance on maintaining chastity and preparing for marriage thoroughly.